Exploring Factors Affecting Consumer Behavioral Intentions toward Online Food Ordering in Thailand - Chidchanok Inthong; Thanapong Champahom; Sajjakaj Jomnonkwao; Vuttichai Chatpattananan; Vatanavongs Ratanavaraha (Sustainability, 2022)
Due to the COVID-19 epidemic, ordering food online has become very popular. This study used a structural equation model to analyze the indicators that influence the decision to order food through a food-delivery platform. The theory of planned behavior and the technology acceptance model were both used, along with a new factor, the task–technology fit (TTF) model, to study platform suitability. Data were collected using a questionnaire given to a group of 1320 consumers. The results showed that attitudes toward on-line delivery most significantly affected the behavioral intentions of the consumers, followed by subjective norms. Among attitudes, perceived ease of use was the most significant, followed by perceived usefulness and trust. The study’s results revealed that TTF had the most significant impact on perceived ease of use, followed by perceived usefulness. This means that, if a food-ordering platform is deemed appropriate, consumers will continue to use it, and business sustainability will be enhanced.
Keywords: Digital Marketing and Social Media; Technology Adoption and User Behaviour; Consumer Retail Behavior Studies